Book Review Present to Prof. Nazlı Alkan - Rahmi Akkılık (Türk Kütüphaneciliği)
This study introduces some articles, interviews and remembrances for retirement of Prof. Nazlı Alkan who is Faculty of Letters member of Ankara University Department of Information and Records Management.